Manajemen Penyelenggaraan Pembelajaran Inklusi Bagi Anak Berkebutuhan Khusus (Studi Kasus SMK Negeri 8 Surakarta) - Kurniawan, Heppy Budi; , Prof. Dr. Bambang Sumardjoko; , Dr. Eko Supriyanto (2015)
Heppy Budi Kurniawan. Q 100 130 050 MANAGEMENT OF THE ORGANIZATION OF LEARNING inclusion of children with special needs in vocational STATE 8 SURAKARTA.Thesis.Surakarta Muhammadiyah University Graduate Program. 2015. Implementation of learning inclusion in SMK Negeri 8 Surakarta based on Decree of ministry National Education Number 70 of 2009 and the designation from the agency offically of Youth and Sports Surakarta. This study aimed to describe the characteristics of the learning model of organizing and inclusion for children with special needs Education in SMK Negeri 8 Surakarta. This type of research used qualitative descriptive research and design research with an ethnographic approach. Research held at SMK Negeri 8 Surakarta with address at Jl. SangiheKepatihanwetan, Jebres, Surakarta. Data obtained through observation, interviews, and documentation in the field. Results of the research is the integrated model, namely the inclusion of learning in SMK Negeri 8 Surakarta ABK students into the classroom together learning with regular child and the curriculum using PPI. Facilities and infrastructure sufficient to support the implementation of learning. Learning the handling characteristics match the type of needs, that the assistance of a teacher to help when experiencing barriers and difficulties in learning. Besides the characteristics of student learning to include crew to perform in a sporting activity and standard minimum completeness criteria (KKM) lower than regular kids.